Аналіз систем та алгоритмів керування автоматичних трансмісій автомобіля - Пельо, Роман (Видавництво Львівської політехніки, 2018)
In the work the analysis of algorithms of control of robotized automatic transmission boxes of cars of leading world manufacturers is carried out. Arguments in favor of the fact that a large number of designs of automotive transmissions and their management algorithms does not indicate a high level of perfection. It is emphasized that there are no differences between the laws of gear shifting, which are optimal for fuel economy or car dynamic.
Analysis of control systems in automatic transmission of automobile
Keywords: 621.83; 658; 652